2011
DOI: 10.1071/fp11016
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant profiling of Hippophae salicifolia growing in sacred forests of Sikkim, India

Abstract: Hippophae commonly known as sea-buckthorn, is a versatile plant with multipurpose uses including the control of soil erosion, biological nitrogen fixation and medicinal properties. In India, two species of sea-buckthorn; namely, Hippophae salicifolia D. Don and Hippophae rhamnoides L., are very common. H. salicifolia has a shrub-to-tree habit and is restricted to the Himalayan region, whereas H. rhamnoides is bushy, growing at higher altitude in India, and widely distributed in Europe and Asia. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…Similar trend shown by the BAE and BME was very similar at 20, 80 and 120 lg/ml. Results were in accordance to previous works on other bamboo species (Goyal et al 2011a;Nagavani and Rao 2010). Mostly, the antioxidant activity in plants is due to the presence of polyphenols (Nakbi et al 2010;Middha et al 2013;Usha et al 2014).…”
Section: Ferric Reducing Power Assay (Frap)supporting
confidence: 81%
See 1 more Smart Citation
“…Similar trend shown by the BAE and BME was very similar at 20, 80 and 120 lg/ml. Results were in accordance to previous works on other bamboo species (Goyal et al 2011a;Nagavani and Rao 2010). Mostly, the antioxidant activity in plants is due to the presence of polyphenols (Nakbi et al 2010;Middha et al 2013;Usha et al 2014).…”
Section: Ferric Reducing Power Assay (Frap)supporting
confidence: 81%
“…Solvent selection was done based on the ethnopharmacological uses of the plants. Previous studies indicate methanol, water and acetone extraction as the most popular solvents used for the plant extraction research (Middha et al 2013(Middha et al , 2016aGoyal et al 2011aGoyal et al , b, 2013.…”
Section: Plant Yieldmentioning
confidence: 99%
“…A recent study by Kruczek et al [36] has showed the antioxidant capacity of crude extracts containing carotenoids from the berries of various cultivars of Seabuckthorn (Hippophae rhamnoides L.). Strong correlation was also observed between DPPH scavenging activity and total phenolic content from all Vinay Kant, et al: Antioxidant potential of seabuckthorn pomace the extracts of two species of sea-buckthorn; namely, Hippophae salicifolia D. Don and Hippophae rhamnoides L. [37] In review of Patel et al, [38] it has been described that seabuckthorn reduced recurrence of angina, ischemic electrocardiogram which might be due to decreased myocardial oxygen consumption and inhibition of platelet aggregation induced by collagen. So, in addition of the antioxidant properties of these extract, they can be validated for the prevention of these complications.…”
Section: Reducing Power Capabilitymentioning
confidence: 97%
“…Auguy et al (2011) provide the first (though preliminary) insights on the involvement of isoflavonoids as signal molecules during C. glauca nodulation. Regarding nodule functioning, Goyal et al (2011) discusses the antioxidant profiling of Hippophae salicifolia from the sacred forests of Sikkim, India. A detailed evaluation of the effects of elevated atmospheric CO 2 concentration, soil nutrients and water conditions on photosynthetic and growth responses of Alnus hirsuta is provided by Tobita et al (2011).…”
Section: The 16th International Meeting On Frankia and Actinorhizal Pmentioning
confidence: 99%